Impact of amplified evaporation due to lake expansion on the water budget across the inner Tibetan Plateau. (14th October 2019) - Song, Chunqiao; Sheng, Yongwei; Zhan, Shengan; Wang, Jida; Ke, Linghong; Liu, Kai
Abstract: Over the past decades, changing climate has exerted pronounced influences on the cryo‐hydrological environment on the Tibetan Plateau. One major manifestation is the widespread lake expansions over Tibetan endorheic basins. The enlarged lake water surface areas are expected to significantly alter land‐atmosphere water fluxes, which in return may pose feedbacks to the climate system and hydrological processes. The goal of this study is to investigate the potential influences of the recent lake expansions on amplifying the evaporation flux over the basins of inner Tibetan Plateau (ITP). We detected that the ITP lakes have experienced a net inundation increase of 4, 542.3 km 2 during 2000–2015, about 95.6% of which was contributed by lakes larger than 1 km 2 . We further estimated the land and water evaporations based on multi‐source, available actual evapotranspiration (ETa) and potential evapotranspiration data sets, and in situ evaporation records. The differences between land ETa and lake water evaporation were employed to represent the evaporation alternation over newly inundated basin (named "land‐to‐lake" hereafter) areas. The land ETa was estimated based on the average of three commonly used gridded data sets while the over‐lake evaporation was calculated by the empirical correction of potential evaporation estimates by spatial interpolation of pan evaporation. A conservative estimate using the pan coefficient of 0.6 indicates that the newly inundated lake area may have led to a potential evaporation increase of 3.08 ± 1.08 Gt/year on the ITP. The increased evaporation flux is close to half of the recent annual growth rate of lake water storage in the ITP. Despite unneglectable uncertainties, our estimates initiate an important assessment of how the recent lake expansion across the ITP has influenced the local land‐atmosphere interactions and the water cycle. Accounting this evaporation amplification is crucial to reduce the uncertainty in estimating basin‐scale water budgets and projecting the regional water balance. Abstract : Spatial pattern of evaporated water budget over the newly inundated lake area across the ITP basins.